2020
DOI: 10.21203/rs.3.rs-52850/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Providers' Definitions of Quality and Barriers to Providing Care: a Qualitative Study in Rural Mpumalanga Province, South Africa

Abstract: Background: Facing a quadruple burden of disease (infectious disease, non-communicable disease, maternal and child mortality, high levels of violence and injury), South Africa requires high-quality primary health care to retain patients and optimize outcomes. National health policy is focused on strengthening primary care. While prior research has identified implementation challenges within the primary health care system, there is less understanding of how providers define quality, their perceptions of barrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…All the health facilities reported inadequate number of expected qualified staffs based on the national guideline especially in the health posts. The impact of inadequate staffs on quality of health care services was also reported in other studies with the shortages of staff leading to short consultation period and increased workload compromising quality of care [11][12][13][14][15]. The studies also reported that high turnover of staff leads to loss of skills and knowledge and most newly employed personnel do not have appropriate work experience and still require training to provide quality health care which may not be provided to them on time [11,12].…”
Section: Discussionmentioning
confidence: 67%
“…All the health facilities reported inadequate number of expected qualified staffs based on the national guideline especially in the health posts. The impact of inadequate staffs on quality of health care services was also reported in other studies with the shortages of staff leading to short consultation period and increased workload compromising quality of care [11][12][13][14][15]. The studies also reported that high turnover of staff leads to loss of skills and knowledge and most newly employed personnel do not have appropriate work experience and still require training to provide quality health care which may not be provided to them on time [11,12].…”
Section: Discussionmentioning
confidence: 67%
“…Within these facilities, access to primary health care and ART is free of charge. However, patient wait times often exceed national standards and there is limited to no differentiated care for young people (21).…”
Section: Methodsmentioning
confidence: 99%